2015
DOI: 10.1080/15384101.2015.1044172
|View full text |Cite
|
Sign up to set email alerts
|

Two-way communication between the metabolic and cell cycle machineries: the molecular basis

Abstract: The relationship between cellular metabolism and the cell cycle machinery is by no means unidirectional. The ability of a cell to enter the cell cycle critically depends on the availability of metabolites. Conversely, the cell cycle machinery commits to regulating metabolic networks in order to support cell survival and proliferation. In this review, we will give an account of how the cell cycle machinery and metabolism are interconnected. Acquiring information on how communication takes place among metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 151 publications
(111 reference statements)
1
65
0
2
Order By: Relevance
“…We showed that treatment of HeLa cells with the PDK inhibitor DCA eliminates the oscillations in glucose flux into TCA cycle, suggesting that cell cycle‐specific regulation of PDH activity may be involved in regulating these flux oscillations. Consistently, PDK4 was reported to be induced by the E2F‐pRB pathway which controls cell entry to S phase (Hsieh et al , ; Kaplon et al , ). Furthermore, analyzing published phosphoproteomics data for HeLa cells measured throughout the cell cycle (Olsen et al , ) shows more than twofold increase in the phosphorylation of the PDH E1 component in early and late S phase versus in G1 (Appendix Fig S18).…”
Section: Discussionmentioning
confidence: 73%
“…We showed that treatment of HeLa cells with the PDK inhibitor DCA eliminates the oscillations in glucose flux into TCA cycle, suggesting that cell cycle‐specific regulation of PDH activity may be involved in regulating these flux oscillations. Consistently, PDK4 was reported to be induced by the E2F‐pRB pathway which controls cell entry to S phase (Hsieh et al , ; Kaplon et al , ). Furthermore, analyzing published phosphoproteomics data for HeLa cells measured throughout the cell cycle (Olsen et al , ) shows more than twofold increase in the phosphorylation of the PDH E1 component in early and late S phase versus in G1 (Appendix Fig S18).…”
Section: Discussionmentioning
confidence: 73%
“…CDK inhibitors are involved in many cellular processes, including cell cycle control, transcription, cell migration and metabolism; and they can affect cell quiescence, senescence, differentiation or cell death, depending on the cellular setting 112, 143, 155, 161164 . In most cases, these functions are mediated by inhibition of specific cyclin–CDK complexes.…”
Section: Control Of Cell Differentiationmentioning
confidence: 99%
“…Further observations that cyclin D1 can directly bind additional lipogenic enzymes and mitochondrial proteins 48 point to cyclin D1 as an important regulator of metabolic activities through different pathways 143 . In addition to cyclin D1, also cyclin E has been proposed to inhibit mitochondrial biogenesis and oxidative metabolism in a transcriptional manner, but the exact mechanism is unknown 144 .…”
Section: Roles Of Cyclins and Cdks In Metabolismmentioning
confidence: 99%
“…9 Furthermore, there is growing evidence supporting the role of cell cycle regulators such as cyclins and cyclin-dependent kinases in the regulation of metabolism. 10 Vpr is known to induce cell cycle arrest in G 2 /M phase. 11,12 Vpr-mediated pathogenesis in macrophages has been extensively investigated, [13][14][15] but its effects on the global molecular mechanism associated with metabolic pathways have not been characterized.…”
Section: Introductionmentioning
confidence: 99%